Why Sexual Assault Kits Were Not Tested: a Systematic Review - Wallenborn, Joslyn K. (Criminology, criminal justice, law & society, 2022)
As a systemic practice, law enforcement across jurisdictions nationwide have not submitted hundreds of thousands of collected sexual assault kits for forensic DNA testing over the past several decades. It is critical to understand why police have been setting aside this valuable evidence, as DNA is a unique and powerful criminal justice tool that can help identify suspects, uncover serial offenders, and exonerate the wrongly convicted. The growing body of research tackling this issue has been largely fragmented by locality and sample, leaving a limited understanding of shared and divergent findings across jurisdictions. Drawing from a body of 16 research articles from 2004 through 2021, the present study brings together findings that span samples and locales to illuminate connections across data that paint a more cohesive picture of how the systemic practice of not submitting sexual assault kits for forensic DNA testing occurred. Through a systematic literature review, it is revealed that research in this area is not dichotomized between decision-making by police based on either practical concerns or extralegal factors, but, rather, it comes together to tell a complex story of why SAKs remained unsubmitted for forensic testing throughout the criminal justice system as a consequence of shared responsibility across several disciplines and how researchers shape this story through the methodological choices they make. Practical multidisciplinary policy considerations are discussed.